Rapid RNA Extraction from Eucalyptus tree and its down processing for cloning of dehydrin genes - Ghulam Zahara Jahangir; Shagufta Naz; Muhammad Idrees Khan; Muhammad Zafar Saleem (Advancements in Life Sciences, 2018)
Background: RNA extraction from tree species like Eucalyptus is very tedious and difficult task. In this study a very short and efficient method of RNA extraction from Eucalyptus has been described.